Physiological effect of iron status on patients with polycystic ovary syndrome in Basrah city: Iron status on patients with polycystic ovary syndrome - Alakabi, Dalal (Journal of Medical Biochemistry, 2022)
Polycystic ovary syndrome (PCOS) is one of the most common gynecological diseases that affect the fertility in women in Basra governorate. The current study was designed in order to assess iron aberrations in PCOS patients by measuring the related parameters and their relationship with sex hormones in patients with PCOS. Serum samples were collected from 45 PCOS patients and 45 controls from a private women’s clinic and were measured by ELISA in a private medical laboratory. The results showed a significant decrease in the level of hepcidin, transferrin and estradiol versus a significant increase in iron, ferritin, progesterone and testosterone. The current study showed a clear imbalance in the level of iron and its serum regulating parameters in in PCOS women, and there is an effective correlation between iron status and sex hormones.